Exact SNR and SIR analysis in Poisson wireless networks - G.P. Efthymoglou; P.S. Bithas; A.G. Kanatas (Electronics Letters)
The probability density function and cumulative distribution function of the received signal‐to‐noise ratio (SNR) and the received signal‐to‐interference ratio (SIR), for interference‐limited systems is derived, at the nth nearest neighbour node in a Poisson point process wireless random network. The analytical expressions are given in terms of the Meijer G‐function and reveal the impact of node spatial density, transmit power, interference power, and path‐loss exponent on the connectivity probability of a broadcast wireless transmission. The analytical results are validated with computer simulation.